Influence of voxel size on micro-CT analysis of debris after root canal preparation - PINTO, Jáder Camilo [UNESP]; TORRES, Fernanda Ferrari Esteves [UNESP]; SANTOS JUNIOR, Airton Oliveira [UNESP]; TAVARES, Karina Ines Medina Carita [UNESP]; GUERREIRO-TANOMARU, Juliane Maria [UNESP]; TANOMARU-FILHO, Mario [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to assess the influence of micro-computed tomography (micro-CT) voxel size on the evaluation of debris accumulation after passive ultrasonic irrigation (PUI) in curved root canals prepared with rotary nickel-titanium files. Mesial root canals (n = 24) of mandibular molars with curvature between 2 5° and 35° were prepared using ProDesign Logic 30/.05 (PDL) or HyFlex EDM 25/.08 (HEDM). PUI was performed after root canal preparation of all root canals. The specimens were scanned using high-resolution (5 μm voxel size) micro-CT imaging before and after experimental procedures. The percentage of debris was analyzed in the middle and apical thirds using images with 5, 10 and 20 μm voxel sizes. Data were compared using unpaired and paired Student's t-test, ANOVA and Tukey's statistical tests (α = 0.05). There were no differences among the debris analyses performed at different voxel sizes (5, 10 and 20 μm) (p > 0.05). The percentage of debris was similar between the root canals prepared by PDL and HEDM before and after PUI (p > 0.05). In both groups, the percentage of debris decreased in the middle third after PUI (p < 0.05). Within the limitations of this ex vivo study, it can be concluded that the voxel sizes evaluated did not have a significant impact on the analysis of accumulated debris. However, the results showed a tendency for detection of more debris in the analysis performed using a lower voxel size. PUI decreased the debris accumulation in the middle third of curved root canals.
Keywords: Dental Instruments; Dental Pulp Cavity; Root Canal Preparation; Ultrasonic Therapy; X-Ray Microtomography